HUBUNGAN PEMBERIAN ASI TOPIKAL PADA TALI PUSAT DENGAN LAMA PELEPASAN TALI PUSAT DI DESA MEGONTEN KEBON AGUNG KAB DEMAK - Munadhoroh; Atun Wigati; Ummi Kulsum (Jurnal Medicare, 2026)
Background: Umbilical cord care involves the treatment and tying of the umbilical cord, which causes the final physical separation between mother and baby. The umbilical cord is then cared for in a sterile, clean, dry, and infection-free condition. The purpose of this study was to determine the effect of topical breast milk application on the time of umbilical cord separation. And to compare the duration of umbilical cord separation between babies given topical breast milk and sterile gauze. Using SOP sheets and observation sheets. Method: The research method used was a quasi-analytical experimental design. The population in this study consisted of all babies born between October and December 2025, totalling 62 babies. Research results: There is a significant relationship or difference between umbilical cord care with topical breast milk and umbilical cord care using sterile gauze. Suggestions: The results of this study can be used to provide knowledge about inexpensive and easy umbilical cord care methods that can support maternal and child health programmes at health centres.